2021
DOI: 10.1097/qad.0000000000002836
|View full text |Cite
|
Sign up to set email alerts
|

Risk of adverse coronavirus disease 2019 outcomes for people living with HIV

Abstract: Objective: To assess whether people living with HIV (PLWH) are at increased risk of coronavirus disease 2019 (COVID-19) mortality or adverse outcomes, and whether antiretroviral therapy (ART) influences this risk. Design: Rapid review with meta-analysis and narrative synthesis. Methods: We searched databases including Embase, Medline, medRxiv and Google Scholar up to 26 August 2020 for studies describing COVID-19 outcomes in PLWH and conducte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
78
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 38 publications
6
78
2
1
Order By: Relevance
“…Clinical studies conducted thus far seem to suggest that TDF, but not TAF, based-ART may reduce COVID-19 incidence, risk of hospitalization and mortality in HIV-infected patients [ 19 , 94 , 95 , 96 ], while a preventive effect of TDF or TAF on COVID-19 is suggested by studies on HIV-negative PrEP users [ 99 ]. Taken together, although the available observational studies are few and do not provide conclusive data on TDF or TAF protective effects, the first compelling evidence suggests that more studies are needed to understand the role of this drug, both in COVID-19 treatment and prevention.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Clinical studies conducted thus far seem to suggest that TDF, but not TAF, based-ART may reduce COVID-19 incidence, risk of hospitalization and mortality in HIV-infected patients [ 19 , 94 , 95 , 96 ], while a preventive effect of TDF or TAF on COVID-19 is suggested by studies on HIV-negative PrEP users [ 99 ]. Taken together, although the available observational studies are few and do not provide conclusive data on TDF or TAF protective effects, the first compelling evidence suggests that more studies are needed to understand the role of this drug, both in COVID-19 treatment and prevention.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis [ 19 ] focused on the risk of several adverse COVID-19 outcomes in HIV-infected patients. The authors identified 11 studies that assessed the impact of ART on COVID-19 outcome in HIV-infected patients with no conclusive results (HIV-infected patients on ART with COVID-19, n = 4726, comprising the studies described above in [ 94 , 95 , 96 ]).…”
Section: Clinical Datamentioning
confidence: 99%
See 2 more Smart Citations
“…In summary, accumulating data direct towards a slightly increased risk of severe COVID-19 outcomes with underlying HIV-1 infection, particularly in patients that are sub-optimally treated and immunocompromised [535]. Studies with higher case numbers with full adjustment of confounders need to confirm these preliminary findings.…”
Section: Interferon Responsementioning
confidence: 94%